Anticipation, free-rider problem, and adaptation to trade union: re-examining the curious case of dissatisfied union members - Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2010)
This paper documents evidence that rejects the paradox of dissatisfied union members. Using eleven waves of the BHPS, it studies the past, contemporaneous, and future effects of union membership on job satisfaction. By separating union free-riders from other nonmembers in the fixed effects equations, I find significant anticipation effects to unionism for prospective members and covered nonmembers of both genders. Workers go on to report, on average, a significant net increase in overall job satisfaction at the year unionization occurs. Nonetheless, adaptation to unionism is complete within the first few years of joining a unionized firm. One hypothesis for this is that workers adapt their reported satisfaction over time to support their union bargaining efforts, which would be consistent with the explanation given by Freeman and Medoff (1984) of union's role in fanning the flame of discontent to the management during contract negotiations.
Keywords: J28; J5; 330; Union coverage; union membership; job satisfaction; anticipation; adaptation; free-rider; longitudinal; Gewerkschaftlicher Organisationsgrad; Mitgliedschaft; Trittbrettfahrerverhalten; Arbeitszufriedenheit; Großbritannien